2015
DOI: 10.1007/s00415-015-7837-x
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of CSF biomarkers using an electrochemiluminescence-based detection system in the differential diagnosis of AD and sCJD

Abstract: The identification of reliable diagnostic tools for the differential diagnosis between sporadic Creutzfeldt-Jakob Disease (sCJD) and Alzheimer's disease (AD) remains impeded by the existing clinical, neuropathological and molecular overlap between both diseases. The development of new tools for the quantitative measurement of biomarkers is gaining experimental momentum due to recent advances in high-throughput screening analysis and with the optimization of assays for their quantification in biological fluids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 40 publications
2
13
0
Order By: Relevance
“…We could confirm previous observations of increased CSF ␣Syn concentrations in CJD (33)(34)(35)(36) and observed also a tendency to elevated concentrations in AD (37)(38)(39). ␣Syn has been suggested as a biomarker for the differential diagnosis of AD and CJD (33) which is supported by our data.…”
Section: Investigation Of Synuclein Origin and Hemolysis As Confoundingsupporting
confidence: 82%
See 1 more Smart Citation
“…We could confirm previous observations of increased CSF ␣Syn concentrations in CJD (33)(34)(35)(36) and observed also a tendency to elevated concentrations in AD (37)(38)(39). ␣Syn has been suggested as a biomarker for the differential diagnosis of AD and CJD (33) which is supported by our data.…”
Section: Investigation Of Synuclein Origin and Hemolysis As Confoundingsupporting
confidence: 82%
“…␣Syn has been suggested as a biomarker for the differential diagnosis of AD and CJD (33) which is supported by our data. However, ␣Syn determination has some drawbacks including susceptibility to blood contamination.…”
Section: Investigation Of Synuclein Origin and Hemolysis As Confoundingsupporting
confidence: 78%
“…Several indications suggested that the U‐plex human aSyn kit test would be a good candidate to validate its potential interlaboratory performance in the diagnosis of sCJD as the final step before its introduction in clinical practice. On one hand, we previously demonstrated the increased sensitivity of electrochemiluminescence platforms over classical colorimetric assays in the quantification of CSF aSyn [6], leading to a better discriminatory power between sCJD and non‐CJD cases. On the other hand, according to the manufacturer, the U‐plex human aSyn kit was developed following “fit for purpose” principles [37] and is consistent with guidance from the Clinical and Laboratory Standards Institute (http://www.clsi.org).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it has been suggested that a-synuclein is specifically regulated in sCJD (Kasai et al, 2014;Llorens et al, 2015a;Mollenhauer et al, 2008a). The underlying mechanism leading to an increase of a-synuclein in the CSF is still unknown.…”
Section: A-synucleinmentioning
confidence: 98%